A Review of ERCC1 Gene in Bladder Cancer: Implications for Carcinogenesis and Resistance to Chemoradiotherapy. (26th October 2011) - Kawashima, Atsunari; Takayama, Hitoshi; Tsujimura, Akira
Abstract : The excision repair cross-complementing group 1 (ERCC1) gene performs a critical incision step in DNA repair and is reported to be correlated with carcinogenesis and resistance to drug or ionizing radiation therapy. We reviewed the correlation between ERCC1 and bladder cancer. In carcinogenesis, several reports discussed the relation between ERCC1 single nucleotide polymorphisms and carcinogenesis in bladder cancer only in case-control studies. Regarding the relation between ERCC1 and resistance to chemoradiotherapy, in vitro and clinical studies indicate that ERCC1 might be related to resistance to radiation therapy rather than cisplatin therapy. It is controversial whether ERCC1 predicts prognosis of bladder cancer treated with cisplatin-based chemotherapy. Tyrosine kinase receptors or endothelial-mesenchymal transition are reported to regulate the expression of ERCC1, and further study is needed to clarify the mechanism of ERCC1 expression and resistance to chemoradiotherapy in vitro and to discover novel therapies for advanced and metastatic bladder cancer.